2017
DOI: 10.7150/jca.17437
|View full text |Cite
|
Sign up to set email alerts
|

Strong Correlation of Indoleamine 2,3-Dioxygenase 1 Expression with Basal-Like Phenotype and Increased Lymphocytic Infiltration in Triple-Negative Breast Cancer

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1) is an immunosuppressive enzyme involved in tumor immune escape. Blockade of the IDO1 pathway is an emerging modality of cancer immunotherapy. Triple-negative breast cancer (TNBC) lacks established therapeutic targets and may be a good candidate for this novel immunotherapeutic agent. The purpose of this study was to evaluate the clinicopathologic characteristics of the IDO1-expressing TNBC subset. A tissue microarray was constructed from 200 patients with TNBC. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…Significantly reduced heterogeneity in the prospective studies suggested that the type and quality of included literature may have affected the level of heterogeneity on OS. Since there was no enough information, our meta-analysis excluded some studies, and most of these studies were consistent with our results [45][46][47]. Only one study showed that high IDO mRNA expression was associated with favorable prognostic value in basal-like breast carcinoma, but this study only provided metastasis-free survival data in basal-like breast carcinoma [48].…”
Section: Discussionsupporting
confidence: 77%
“…Significantly reduced heterogeneity in the prospective studies suggested that the type and quality of included literature may have affected the level of heterogeneity on OS. Since there was no enough information, our meta-analysis excluded some studies, and most of these studies were consistent with our results [45][46][47]. Only one study showed that high IDO mRNA expression was associated with favorable prognostic value in basal-like breast carcinoma, but this study only provided metastasis-free survival data in basal-like breast carcinoma [48].…”
Section: Discussionsupporting
confidence: 77%
“…Subsequent studies in murine models have revealed that IDO plays a key role in preventing a host of autoimmune conditions . Work in malignancy has revealed IDO expression in a variety of solid tumour types, including non‐small‐cell lung carcinoma, colorectal carcinoma, breast carcinoma and a variety of gynaecological malignancies . Furthermore, multiple studies have shown enhanced IDO expression at the tumour–stromal interface and in areas of lymphocytic infiltration, suggesting an adaptive mechanism of immune evasion similar to that described with PD‐L1 .…”
Section: Discussionmentioning
confidence: 90%
“…It is therefore not surprising that tumors with high TIL infiltrate will also have an increase in the expression of PD-L1 and IDO. A recent study by Kim et al, where IDO1 protein expression was studied in 200 TNBC patients, found that over 50% of basal-like TNBC expressed IDO1 [ 43 ]. Epacadostat is an IDO1 inhibitor which has been shown to increase and restore the proliferation of dendritic cells, NK and T cells, but reduce Tregs.…”
Section: Future Of Immunotherapy (It) In Breast Cancer (Bc)mentioning
confidence: 99%